(untitled) (Al-Qamar, 2022)
Every civilization carries forward the tradition of derivation and acceptance from previous civilizations. In known civilizations all human sciences and arts begin with the Greek civilization. Islamic civilization is the benefactor of humanity as a whole. In the era of Islamic civilization, not only the intellectual heritage of previous civilizations was preserved, but new sciences and arts were introduced. Islamic civilization created a new hope for research and exploration in the human mind by presenting the idea of conquering the universe. The phenomena of nature, which were previously considered invincible, Islamic civilization, said that they were created for human beings. The theoretical beginning of modern science was the result of this intellectual revolution of Islamic civilization. Islamic civilization not only promoted other sciences and arts, but also brought astronomy to its peak. The art of astronomy deserved the special attention of Muslims as it was associated with the religious orders of Muslims. Therefore, Muslim experts acquired special skills in this art. After decline of Islamic civilization, when this art was transferred from Arabs to Europe, hundreds of Arabic words and terms were transferred into Latin and English. Even today, most of the names of stars are Arabic origin. In this article, we have compiled a list of English words and terms having Arabic origin as well as name of stars which has Arabic origin. For those who are interested in more, the original references has also been given, which can be used.